ANALISIS KECENDERUNGAN PEMBELIAN SECARA IMPULSIF DITINJAU DARI SUDUT PANDANG ISLAM - Rina Samsiyah Agustina; Azka Muhammad Mufti; Ima Rahmawati; Irni Fahrani (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2024)
The needs of modern consumers are often influenced by capitalist lifestyles that complicate the understanding between needs and wants. Impulse buying is a common phenomenon that raises questions about the compatibility of this consumptive practice with Islamic teachings that emphasize balance and justice. This study aims to analyze impulse buying tendencies from an Islamic perspective. Through a qualitative descriptive approach, this research analyzes various relevant literatures to understand the factors that drive impulse buying and its implications in the context of Islamic values. The results show that impulse buying often violates the principle of istishab (continuity) in Islam and can lead to unhealthy consumptive behavior that is financially and spiritually detrimental. Therefore, a deeper understanding of Islamic teachings and values and the application of these practices in daily life is expected to help Muslims overcome impulse buying tendencies and develop more balanced and responsible consumption patterns.